In-situ measurement and prediction of traffic noise transmission loss across a residential flat unit façade installed with two plenum windows - Tang, Shiu Keung; Li, Xiaolong (Institute of Noise Control Engineering of the USA, 2020)
In the present study, the traffic noise transmission loss across a residential flat unit façade installed with two plenum windows are measured in-situ in a 30-storey high-rise building located in an opened environment next to a very busy and noisy main trunk road. These plenum windows are intended to help reduce noise exposure of the residents and at the same time allow for a reasonable level of natural ventilation. Empirical scheme to predict these transmission losses is also developed. The results show that the traffic noise transmission losses of plenum windows adopted in this housing block are only weakly dependent on elevation from the trunk road. The corresponding predictions agree very well with site measurement results with a root-mean-square deviation of about 0.8 dBA.